Plasma dicing technology - Matsubara, Noriyuki; Windemuth, Reinhard; Mitsuru, Hiroshima; Atsushi, Harikai (2012 4th Electronic System-Integration Technology Conference, 2012)
Conventional methods for wafer dicing like mechanical or laser dicing solution are showing some limitations. Plasma dicing process was designed to overcome such limitations regarding chip damage and throughput which is discussed in comparison with conventional dicing methods. Typical overall process flow is explained in detail. Some examples of etching results are shown. Solutions for round-corner-etching are explained. We will give better understanding of future solutions for dicing process by use of plasma.